INTENT SUICIDE AS A FACTOR RISK ON PERSONS WITH MENTAL HEALTH PROBLEMS - Dervishi, Eglantina; Shehu, Artemisa; Ostreni, Vera; Zhilla, Eralda (European Scientific Journal, ESJ, 2015)
Objective: The purpose of this study is to present an overview of suicide intent in subjects who were submitted at emergency first aid at the Psychiatric Clinic and to highlight the relation between suicide intent, psychiatric diagnosis, and demographic data such as gender, age and social status. Methods: Collected data are based on recording statistics at the Emergency Psychiatric Clinic, Hospital University Center "Mother Theresa", Tirana, Albania. Analyses of the data were made by a group searching through quantitative methods focusing on admissions statistics and identification of intented suicide during a three-year period from 2011- 2014 . Results: Attempted suicide have a significant relation with a psychiatric diagnosis. Demographic variables such as gender, occupational status, marital status and place of residence were not found to have a link with suicidal attempts. The presence of psychiatric disorders emerge as the key in determining suicidal attempts. Conclusion: Research confirms the influence of psychiatric diagnsosis, where mood disorders are of broad expandure to intent suicide in the treated population of Psychiatric Clinic. A hight relationship was between suicide intent and bipolar depression, schizoaffective disorder, major depression with psychotic traits, major depression.